2010
DOI: 10.3758/app.72.5.1311
|View full text |Cite
|
Sign up to set email alerts
|

Isoluminant motion onset captures attention

Abstract: In their 2003 article, Abrams and Christ found that the onset of motion captured attention more effectively than either the offset of motion or continuous motion. Abrams and Christ conceptualized the capture to be occurring at a level higher than does detection of luminance changes in the stimulus. To examine this claim, in the present experiments we replicated their critical experiment but used isoluminant stimuli, which do not produce the low-level luminance transients typically associated with motion. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…The present study examined the effect of the observer's mode of action on the attentional prioritization of visual items on the basis of abrupt motion onset (Abrams & Christ, 2003;Al-Aidroos et al, 2010;Franconeri & Simons, 2003;Guo et al, 2010). Motivated by the common-coding theoretical account of action and perceptual processes (Hommel et al, 2001;Müsseler, 1999;Prinz, 1997), we hypothesized that preparing an action would decrease the availability of features belonging to the prepared action for visual processes, thus reducing attentional capture by an irrelevant motion that is similar to the Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study examined the effect of the observer's mode of action on the attentional prioritization of visual items on the basis of abrupt motion onset (Abrams & Christ, 2003;Al-Aidroos et al, 2010;Franconeri & Simons, 2003;Guo et al, 2010). Motivated by the common-coding theoretical account of action and perceptual processes (Hommel et al, 2001;Müsseler, 1999;Prinz, 1997), we hypothesized that preparing an action would decrease the availability of features belonging to the prepared action for visual processes, thus reducing attentional capture by an irrelevant motion that is similar to the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiments, we employed a version of the attentional-capture-by-motion-onset paradigm (Abrams & Christ, 2003;Al-Aidroos et al, 2010;Franconeri & Simons, 2003;Guo et al, 2010) in which subjects searched for a target letter-with two possible identities-among a set size of four items (i.e., one target and three distractors). The critical addition to the paradigm was that the responses were hand movements (via the computer mouse) along either a horizontal or vertical predetermined axis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These reflexive shifts of attention can briefly enhance visual processing with little if any volitional effort from the observer. Events with high feature salience, such as an abruptly appearing object (Jonides, 1981, Yantis and Jonides, 1984; Yantis and Hillstrom, 1994;), an abrupt luminance change (Posner, 1980; Atchley et al, 2000; Snowden, 2002; Theeuwes, 1995), or the onset of motion (Abrams & Christ, 2003; Folk et al, 1994; Guo et al, 2010) have been shown to capture attention and bias visual processing.…”
Section: Introductionmentioning
confidence: 99%